ANALYSIS OF THE FACTORS AFFECTING THE PERFORMANCE OF INDONESIAN EQUITY FUNDS IN 2019-2022 - Setiawan, Dito; Mukhtar, Saparuddin; Zahra, Siti Fatimah (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2024)
The fund manager's approach to managing mutual funds has an impact on the performance of the funds. The performance of mutual funds, which rise annually, is a good indicator of fund managers' ability to manage them effectively. The goal of this research is to ascertain how fund cash flow, market timing ability, and stock selection ability affect equity fund performance from 2019 to 2022. Applying the technique of purposive sampling, this research sample consists of 17 equity funds products chosen based on the research criteria. The research makes use of the prospectus of equity mutual fund products from 2019 to 2022, interest rates, Composite Stock Price Index (IHSG), and Net Asset Value (NAV) of mutual funds every month. The study used panel data regression method with Common Effect Model (CEM) approach. The results of the study show that stock selection ability and fund cash flow have a positive and significant effect on the performance of equity mutual funds. Meanwhile, market timing ability has a positive but insignificant effect on the equity funds performance for the 2019-2022 period.